Large-scale organoid study suggests effects of trisomy 21 on early fetal neurodevelopment are more subtle than variability between isogenic lines and experiments - Czerminski, Jan T.; King, Oliver D.; Lawrence, Jeanne B. (Frontiers in Neuroscience, 2023)
This study examines cortical organoids generated from a panel of isogenic trisomic and disomic iPSC lines (subclones) as a model of early fetal brain development in Down syndrome. An initial study comparing organoids from one trisomic and one disomic line showed many genome-wide transcriptomic differences and modest differences in cell-type proportions that suggested a potential neurodevelopmental phenotype due to trisomy of chr 21. To better control for multiple sources of variation, we undertook a more robust study of ~1,200 organoids using an expanded panel of six all-isogenic lines, three disomic and three trisomic. The power of this experimental design was indicated by strong detection of the ~1.5-fold difference in chr21 genes. However, the numerous expression differences in non-chr21 genes in the smaller study fell away, and the differences in cell-type representation between lines did not correlate with trisomy for chr21. With correction of cell-type proportions, a few non-chr21 genes showed differences, which are discussed. Results suggest that the initial smaller study picked up differences between individual isogenic lines, which “averaged out” in the larger panel of isogenic lines. Our results indicate that even when organoid and batch variability are better controlled, common, subtle differences between isogenic cell lines (even subclones) may obscure, or be confused with, differences due to Trisomy 21. Interestingly, despite some variability between lines and the “fetal stage” of these organoids, an increase in secreted Ab40 peptide levels – an Alzheimer-related phenotype – was clearly observed to correlate with trisomy 21 status. In contrast, results suggest that any neurodevelopmental phenotypes which may be present in ~2nd trimester of DS brain development may be more subtle, and within the variation of neurodifferentiation potential of our isogenic iPSC lines.